A high-quality, chromosome-level genome assembly of the Black Soldier Fly (Hermetia illucens L.) - Tomas N Generalovic; Shane A McCarthy; Ian A Warren; Jonathan M D Wood; James Torrance; Ying Sims; Michael Quail; Kerstin Howe; Miha Pipan; Richard Durbin; Chris D Jiggins (G3: Genes, Genomes, Genetics, 2021)
Abstract Hermetia illucens